teknika EVALUASI TATA KELOLA TEKNOLOGI NFORMASI PADA BPPRD KOTA BANDAR LAMPUNG BANDAR LAMPUNG MENGGUNAKAN FRAMEWORK COBIT 5 DAN BALANCED SCORECARD: EVALUATION OF INFORMATION TECHNOLOGY GOVERNANCE AT BPPRD BANDAR LAMPUNG CITY BANDAR LAMPUNG USES FRAMEWORK COBIT 5 AND BALANCED SCORECARD - Kurniawan, Aris; Triloka, Joko (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2024)
This study identifies issues related to gaps in the performance of Information Technology (IT) governance at BAPENDA Kota Bandar Lampung, which could hinder the achievement of organizational goals and compliance with SPBE regulations. The primary aim of this research is to assess and identify areas needing improvement in IT governance using the COBIT 5 and Balanced Scorecard frameworks. The methodology applied includes measuring maturity levels and analyzing gaps across five main IT domains: Event Management, Incident Management & Request Fulfilment, Problem Management, Service Continuity Management, and Information Security Management. The findings indicate significant gaps with an average GAP of 2.10, highlighting the need for improvements in various aspects of IT governance. This research also provides improvement recommendations based on the Balanced Scorecard, which are expected to help BAPENDA Kota Bandar Lampung enhance the effectiveness and efficiency of IT management to support the overall achievement of organizational goals. Â  Keywords: Cobit 5, Balanced Scorecard method, SPBE.